Chemotherapeutic Challenge: A Case of Acute Kidney Injury During Breast Cancer Management - Kakaraparthy, Ravishankar; Palivela, Nandini; Karri, Lakshya Gayathri Reddy (Indian Journal of Pharmacy Practice)
Acute Kidney Injury (AKI) represents a significant and potentially life-threatening complication, especially in patients undergoing treatment with chemotherapeutic agents. Numerous chemotherapy medications have been associated with nephrotoxicity through various mechanisms, including direct tubular injury, fluid depletion, and disturbances in electrolyte balance. This case analysis underscores the crucial importance of continuous renal function monitoring in cancer patients undergoing systemic chemotherapy. We present the case of a 45-year-old female diagnosed with early-stage breast cancer, who also had notable comorbidities such as type 2 diabetes mellitus, hypertension, and a prior cerebrovascular event. Following her initial cycle of combination chemotherapy using cyclophosphamide and doxorubicin, the patient experienced an episode of AKI. Clinical assessment revealed indications of dehydration and potential nephrotoxic effects. Laboratory tests revealed significantly elevated markers of renal function, while imaging studies showed mild to moderate hepatomegaly, along with alterations in the renal parenchyma. The timely recognition of her condition, alongside appropriate supportive measures, facilitated a complete recovery and successfully averted the risk of irreversible kidney damage.
Keywords: Acute kidney injury; Chemotherapeutic agents; Breast cancer; Comorbidities; Nephrotoxicity; Renal toxicity